2016
DOI: 10.1039/c6ra09759f
|View full text |Cite
|
Sign up to set email alerts
|

Flame retardant plasticized poly(vinyl chloride) film with selective solar spectral transparent properties

Abstract: In this work, some additives were added into plasticized poly(vinyl chloride) (PVC) matrix for the purpose of shielding ultraviolet light (UV), high-energy visible light (HEV) and near-infrared light (NIR). Furthermore, the flame retardance of the plasticized PVC films were also enhanced by adding organo-phosphorus flame retardant plasticizer such as tris(1-chloropropan-2-yl) phosphate (TCPP). The properties of PVC films were investigated by the limiting oxygen index (LOI) test and ultraviolet-visible-near-inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…In our previous work, polyester‐plasticized PVC films with ultraviolet and high‐energy visible (HEV) light shielding performance have been achieved by adding UVAs and pigment yellow (PY) . However, whether these amazing optical performances can be kept after photo‐degradation was still in doubt.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous work, polyester‐plasticized PVC films with ultraviolet and high‐energy visible (HEV) light shielding performance have been achieved by adding UVAs and pigment yellow (PY) . However, whether these amazing optical performances can be kept after photo‐degradation was still in doubt.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous work, [22] polyester-plasticized PVC films with ultraviolet and high-energy visible (HEV) light shielding performance have been achieved by adding UVAs and pigment yellow (PY). [23] However, whether these amazing optical performances can be kept after photo-degradation was still in doubt. In order to prolong the longevity of the polyesterplasticized PVC film with desired performance, HALS together with UVAs were added in this paper.…”
Section: Introductionmentioning
confidence: 99%
“…An effect way to improve the ame retardancy of PVC materials is to add ame retardants such as antimony trioxide (Sb 2 O 3 ), 14 alumina trihydrate, Al(OH) 3 , 15 or tripentyl phosphate, trimethyl phosphate, tris(chloropropyl) phosphate, and di-noctylphenyl phosphate, 16 but the addition of ame retardants usually decreases the mechanical properties of PVC blends. It is necessary to prepare PVC materials using ame retardant plasticizers that can effectively improve both the mechanical and ame retardant properties of the PVC blends.…”
Section: Introductionmentioning
confidence: 99%
“…The result is in accordance with the HCl release profile. After Cl was removed, the molecular chains of PVC began to form a reticular structure, which can enhance the heat insulation and the flame‐retardant properties of PVC . Since the EDS scanning is not sensitive of some metal elements, the account for the metal elements is at a low level in the EDS test.…”
Section: Resultsmentioning
confidence: 99%
“…After Cl was removed, the molecular chains of PVC began to form a reticular structure, which can enhance the heat insulation and the flame-retardant properties of PVC. 23 Since the EDS scanning is not sensitive of some metal elements, the account for the metal elements is at a low level in the EDS test. From the EDS test, it is found that these two kinds of LDH have the catalytic dechlorination effect, which makes…”
Section: The Char Analysis Of the Compositesmentioning
confidence: 99%